PENGEMBANGAN MEDIA KOTAK MEMBACA CERDAS PADA PEMBELAJARAN MEMBACA PERMULAAN DI KELAS 1 SDN BILAPORAH 1 BANGKALAN - Hasanah, Alfiatul; Fauziah, Humairah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research and development study aims to develop the Kotak Membaca Cerdas (Smart Reading Box) product for early reading instruction in Grade I at SDN Bilaporah 1 Bangkalan, ensuring that the product is valid, effective, and appealing. This study employed the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this research were Grade I students at UPTD SD Negeri Bilaporah 1 Bangkalan. The validation results from the learning media expert showed a percentage of 94%, categorized as very valid. Validation from the language and material expert obtained a percentage of 88%, categorized as very valid, while validation from the instructional design expert obtained a percentage of 93%, also categorized as very valid. The effectiveness of the media was demonstrated by an average student activity score of 96%, categorized as effective and suitable for use. In addition, student learning outcomes analyzed using the classical completeness formula showed a completeness rate of 100%. The attractiveness of the media was measured through a student response questionnaire, which obtained a score of 99%, categorized as very attractive. Based on these results, the Kotak Membaca Cerdas learning media is declared very valid, effective, and attractive for use in early reading instruction for Grade I elementary school students.